Net-zero buildings: when carbon and energy metrics diverge - Anna Parkin; Manuel Herrera; David A. Coley (Buildings & Cities, 2020)
Many climate change-related building frameworks are designed to improve environmental performance by requiring reduced net energy demand, as it is widely assumed that energy demand ('e.g.' delivered/final, primary, primary non-renewable) is a good proxy for carbon emissions. However, energy grids are becoming less carbon intensive, meaning that the climate change mitigation value of renewably generated energy is not static, and is likely to decrease. In this research, a global integrated building carbon and energy model was created to explore how assessed building performance responded to stepwise variation in multiple building features. Operational and embodied metrics were measured concurrently on the basis of carbon emissions and delivered final energy demand, and included renewable energy generation (via roof-mounted photovoltaics), resulting in two 12.3 million-point data sets. Logistic regression was used to identify patterns in the data sets using binary building classifications (zero or non-zero energy or carbon). The results demonstrate that the profiles of the energy and carbon metric data sets do not mirror each other, indicating that a delivered energy demand assessment is not necessarily a good proxy for carbon emissions. The divergence of these metrics is likely to grow in future as energy grids are increasingly decarbonised.   'Policy relevance' The energy metric is often relied upon as an indicator of climate-related building performance. However, policy-makers and designers should instead focus their attention on a carbon metric in order to achieve the drastic reduction in carbon emissions needed for the 1.5°C limit on rising global temperatures. Grid generated energy (particularly electricity) tends to be viewed as universally carbon intensive, so offsetting even a small amount with renewable energy is seen as beneficial. This research demonstrates that design philosophies underpinning zero-energy building (ZEB) assessment outcomes are likely to be driven by environmental factors ('i.e.' overcoming temperature and insolation challenges). However, the zero-carbon equivalent is likely to be more closely associated with the characteristics of the electricity grid servicing the building. This study highlights the fact that, to accrue real benefits, long-term policy and design decisions need to factor in the changing nature of the carbon implications of energy demand and generation.